A database of words and pictures for investigating phonological-semantic processing and interaction in language processing: Validation and application - Laura Anna Ciaccio; Luigi Grisoni; Sabrina Nieswand; Friedemann Pulvermüller (PLoS ONE, 2025)
An increasing number of studies aim to directly compare aspects of linguistic processing in word production and comprehension using controlled experiments with shared stimuli across modalities. However, the available resources allowing for such investigations are scarce, particularly for languages other than English. To address this gap, we present an open-source database of 151 German words and related picture stimuli. The items are drawn from two well-investigated semantic categories – animals and tools – and differ phonologically by either starting with a labial or a coronal speech sound. The database includes human ratings for depictive accuracy, familiarity, action relatedness, valence, arousal of the pictures, and familiarity, action relatedness, valence, arousal, and imageability of the words. In a set of analyses, we show that the ratings we collected have good reliability and external validity, and align well with previously obtained data from lexical and pictorial databases. The database is complemented with comprehensive information about phonetic/phonological, lexical, morphological, and semantic properties of the words, as well as about luminosity and visual complexity of the corresponding pictures. We finally present a matched stimulus set obtained from the database, as a ready-to-use resource for psycho- and neurolinguistic studies examining semantic and phonological processing along with their interaction in language production and comprehension. The word-picture database, together with the matched stimulus set, are freely available at https://osf.io/k64nh/ .